Expressão de VEGF-C, VEGF-D, mensuração da densidade linfática e da proliferação endotelial linfática em neoplasias de glândulas salivar - Barroso, Keila Martha Amorim (2014)
Salivary gland neoplasms exhibit a great morphological diversity and varied biological behavior which raises the interest in the study of these lesions. The spread of tumor cells is an early step in the progression of malignancies and the neoformed lymphatic vessels are considered essential in tumor dissemination. Vascular endotelial growth fator (VEGF) is a family of proteins involved in angiogenesis e lymphangiogenesis. However, in salivar tumors we have limited information on the expression. The aim of this study was to assess the expression of VEGF-C and VEGF-D, lymphatic vessel density (single-staining D2-40) and lymphatic endothelial proliferation (double labeling D2-40/Ki-67) in a series of salivary glands neoplasms. We selected 20 cases of pleomorphic adenoma, 20 of mucoepidermoide carcinoma, 20 of adenoid cystic carcinoma and 10 tissue sample of normal salivary gland. All cases studied showed positive expression of VEGF-C in intratumoral and peritumoral region, no differences in immunoreactivity was found between the groups. However, the group of adenoid cystic carcinoma showed a significant difference in immunoreactivity of VEGF-C by the cribriform and solid pattern (p = 0.004). Most of the cases included in this study showed weak immunoreactivity for VEGF-D in intratumoral and peritumoral region. In the assessment of lymphatic endotelial density peritumoral, intratumoral and total, the groups showed an increasing gradient, with lower values for the group of pleomorphic adenomas followed by mucoepidermoid carcinoma and adenoid cystic carcinoma. Lymphatic endothelial cell density was higher in malignant than benign tumors. No correlation was observed between the immunoreactivity of VEGF-C and VEGF-D in relation to tumor lymphatic density and lymphatic endothelial proliferation